Application of Coffee Grounds (Coffea sp.) for Macro and Micro Nutrient Production in Mangosteen Peel (Garcinia mangostana L.) Compost - Melita Melita; Mistia Sari; Sanny Edinov; Rezi Junialdi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Mangosteen peel waste (Garcinia Mangostana L) is mixed with coffee grounds (Coffea Sp) to make compost, aiming to return organic matter to the soil and increase fertility. This study looks at the effectiveness of EM4 activator and dry leaves in composting mangosteen peel waste. There are two treatments: mangosteen peel, coffee grounds (KA), mangosteen peel, coffee grounds, dry leaves, EM4 (KADE). As a result, the addition of EM4 and dry leaves increases the composting speed in 31 days, using a C/N ratio reaching 4,79%, according to SNI stndards. The nutrient content in the compost also meets SNI 19-7030-2004 standards, using analysis providing levels of nitrogen, phosphorus, potassium, organic C, and water content thatare suitable for use. The study is recommended to beapplied to several types of plants in appropriate soil pH conditions. It is also recommended to make compost from mangosteen peel in the form of organic fertilizer.